The Importance of Global Value Chain Formation under Digital Policies: An Analytical Study of the Impact of Digital Sovereignty on International Trade Patterns - Sahar Kareem Gatae Ali (International Journal on Economics, Finance and Sustainable Development, 2026)
The research aims to analysis importance formation chains value global in shadow Escalation Policies Digital and growth Heading countries about Sovereignty Digital, with the focus on effect This is amazing Transformations in Patterns commerce International during The period 2018–2024 in all from States United China Germany Korea Southern And Singapore . And it starts Search from hypothesis Basic Its meaning that Transformation digital did not It is merely factor assistant in Strengthening commerce Global, but rather become element Structurally He returns formation chains Value via re distribution stages Production Services Approved on Data and technologies Digital, and appearance Patterns New from organization Economic It is characterized Increasingly blocs Digital And it declined openness Global Traditional . As well . It is clear Search that Policies Related With sovereignty Digital, like legislation protection Data and restrictions on flow Information Contributed in re Structure chains Value Global about More from Retail Geopolitics and competition Technological between forces The major one . And it concludes Search to that States United China They represent Two models Different in Governance Digital, while Seeking Germany to investigation balance between Manufacturing Applicant and organization European, And strengthen Korea Southern Its location in chains Similarities connectors Global, in when Stand out Singapore As a center mediator pivotal in flows Data and trade Digital, Which Reflects transmission Economy Global to model more Complexity He does On " Globalization" Restricted Digitally and re- identification concept Value in Economy International.